Ray Casting With ?On-the-Fly? Region Growing 3-D Navigation Into Cardiac MSCT Volume. - Coatrieux, J.-L (IEEE Transactions on information technology in biomedicine)
This paper describes an extended ray casting scheme for three-dimensional (3-D) navigation into the heart cavities for preoperative planning using multislice X-ray computed tomography data. The key benefit is that artifacts due to contrast inhomogeneities can be eliminated during volume traversal, thus improving the visual perception of the endocardial wall